Association between the BDNF G196A and C270T polymorphisms and Parkinson's disease: a meta-analysis. (1st October 2013) - Dai, Limeng; Wang, Dongmei; Meng, Hui; Zhang, Kun; Fu, Liyuan; Wu, Yuanyuan; Bai, Yun
<x xml:space="preserve">Abstract</x> Epidemiological studies have evaluated the associations between brain-derived neurotrophic factor (BDNF) polymorphisms and Parkinson's disease (PD) risk. However, the results remain inconsistent. Therefore, we conducted a meta-analysis of published case-control studies to better understand these results. Systematic searches of electronic databases Embase, PubMed and Web of Science, as well as hand searching of the references of identified articles were performed. The pooled odds ratio (OR) with 95% confidence interval (CI) were calculated. All the statistical tests were performed using Review Manager 5.1 and Stata 11.0. A total of 13 case-control studies were included, involving two polymorphisms (G196A and C270T) of BDNF gene and covering 3333 PD cases and 3418 controls. No significant associations were found on the overall analysis both G196A and C270T polymorphisms. In the subgroup analysis by ethnicity (Caucasian, Asian and Mixed population), there were still no detectable associations. In conclusion, there is no enough evidence for associations between BDNF polymorphisms (G196A and C270T) and PD risk at present. Larger sample-size and multiethnicity studies with homogeneous PD patients and well-matched controls are needed in the future study.